FORMULATION OF KATUK (Sauropus androgynus L. Merr) LEAVEN EXTRACT EFFERVESCENT AID WITH VARIATIONS OF PEG 6000 LUBRICANT CONCENTRATION - Eka Fitri Yanti; Revano Arnawinata; Nuri; Mohammad Rofik Usman (LPPM Universitas dr. Soebandi, 2025)
Katuk leaves are one type of herbal galactagogue that can increase prolactin and oxytocin levels, and contain nutrients that can be used to facilitate breast milk. This study aims to determine the optimal PEG 6000 Lubricant concentration variation that produces effervescent tablet physical properties that meet the physical properties test requirements. This research is a preexperimental laboratories research. The concentration variation of PEG 6000 lubricant used was 1%, 2% and 3%. Tablets were evaluated for their physical properties including organoleptics, weight uniformity, dissolving time, hardness, pH and fragility. The results of this study indicate that the physical properties of effervescent tablets from katuk leaf extract (S. androgynus) with varying concentrations of PEG 6000 Lubricant meet the requirements of physical properties of Organoleptics, Weight Uniformity, Dissolving Time and Fragility. However, the physical properties of hardness and pH value have not met the requirements of the physical properties test set, the effect of variations in the concentration of PEG 6000 Lubricant on the physical properties of effervescent tablets, namely on Weight Uniformity, Dissolving Time, Hardness test, pH test and Friability test. But in the Organoleptical test, Weight Uniformity, Dissolving Time does not give the effect of differences in lubricant concentration variations